A Rapid Tandem Knoevenagel/Michael Reaction Using Mohr’s Salt as a Highly Efficient Catalyst: Green Synthesis of Bis(pyrazolyl)methanes - Eskandari, Khalil; Karami, Bahador; Khodabakhshi, Saeed; Farahi, Mahnaz (Letters in Organic Chemistry, 2015)
A convenient access to some new and known bis(pyrazolyl)methanes synthesis has been successfully achieved via an alternative Knoevenagel/Michael reaction of aromatic aldehydes and pyrazole-5-one in the presence of Mohr’s salt as a green catalyst. This novel procedure has some advantages such as high efficiency, simplicity, high rate and environmental safety.
Keywords: bis(pyrazolyl)methane